Adverse impact of banana Xanthomonas Wilt on farmers’ livelihoods in Eastern and Central Africa - Nkuba, J.; Tinzaara, William; Night, G.; Niko, N.; Jogo, W.; Ndyetabula, I.; Mukandala, L.; Ndayihazamaso, P.; Niyongere, C.; Gaidashova, S.V.; Rwomushana, I.; Opio, F.; et al. (Academic Journals, 2015)
Banana is a key crop in the livelihoods of many people in the Great Lakes region of East and Central Africa. For more than a decade now, the crop has been threatened by Banana Xanthomonas Wilt (BXW) which has spread throughout the region but at different rates. The disease attacks all banana cultivars and can cause up to 100% yield losses at farm level if effective control measures are not put in place. However, limited information on impact of BXW at regional level is available to guide interventions. Thus, this study assessed the impact of BXW on farmers’ livelihoods in Kagera basin of Tanzania, Burundi and Rwanda. A total of 436 households (Tanzania 120, Burundi 208 and Rwanda 108) mostly from major banana-producing and BXW-affected districts were sampled and interviewed in a household survey. Thirty-three to seventy-five of the total banana mats per farm in the three countries were infected with BXW. Banana production losses caused by BXW were valued at US$ 10.2 million and US$ 2.95 million in Tanzania and Rwanda, respectively, banana sales by farmers dropped by 35% while bunch prices unpredictably doubled. Since banana is a key component of these farming communities, the banana production losses resulted in significant reduction in household food security and incomes. To cope with these challenges, most households are diversifying into other food crops such as maize, cassava and sweet potatoes. This poses a number of socio-economic and biological implications that require further investigation.